A protective role for APP in nuclear waste clearance via lysosomal exocytosis - Godfried Dougnon; Takayoshi Otsuka; Yuka Nakamura; Akiko Sakai; Tomoyuki Yamanaka; Noriko Matsui; Asa Nakahara; Ai Ito; Atsushi Hatano; Masaki Matsumoto; Hironaka Igarashi; Akiyoshi Kakita; et al. (Proceedings of the National Academy of Sciences, 2026)
Amyloid precursor protein (APP) is widely known for its role in Alzheimer’s disease (AD) pathogenesis through its proteolytic processing into amyloid-β peptides. However, its physiological functions remain incompletely understood. Here, we uncover a protective role for full-length APP in facilitating the disposal of nuclear-derived debris under genotoxic stress. In both cultured cells and in vivo mouse models, loss of APP leads to nuclear waste accumulation, increased inflammation, and cell death, whereas APP overexpression mitigates these effects. Mechanistically, we show that APP supports the extracellular release of nuclear waste material through lysosomal exocytosis. APP mutants associated with familial AD fail to mediate this process. Consistently, human AD brain tissue exhibits abnormal nuclear morphology, accumulation of nuclear waste in the cytoplasm, and reduced APP levels per neuron. These findings highlight a conserved cellular mechanism by which APP contributes to nuclear and cellular homeostasis, and suggest that impaired nuclear waste clearance may represent an underappreciated contributor to neurodegeneration.